Socio-pragmatic representation of animal in Al-Bahah proverbs: an eco-linguistic analysis - ALGHAMDI, N. A (Utopía y Praxis Latinoamericana, 2019)
ABSTRACTThe present study aims to reconstruct a synchronic eco-linguistic analysis of Al-Bahah animal proverbs to deduce the representation of the human-animal relationship. The collected data attested four classifications of Al-Bahah animal proverbs and proverb-like expressions into general truth, cultural, social, and apothegm groups. The study reveals that Al-Bahah animal proverbs are not only sociolinguistic-specific but also ecological-specific. To interpret the relevance of these animal proverbs to the Al-Bahah ecosystem, methodologically this study moves along two lines of analysis: a linguistic analysis of metaphorical proverbs, and the social analysis. The present study highlights the Al-Bahah culture and oral tradition. RESUMENEl presente estudio tiene como objetivo reconstruir un análisis eco-lingüístico sincrónico de los proverbios de animales de Al-Bahah. Los datos recopilados atestiguaron cuatro clasificaciones de los proverbios de animales de Al-Bahah y expresiones similares a los proverbios. El estudio revela que los proverbios de animales de Al-Bahah no son solo sociolingüísticos -específicos, sino también ecológico-específicos. Para interpretar la relevancia de estos proverbios animales para el ecosistema de Al-Bahah, metodológicamente este estudio se mueve a lo largo de dos líneas de análisis: un análisis lingüístico de los proverbios metafóricos y el análisis social. El presente estudio destaca la cultura y la tradición oral de Al-Bahah.